Test-time augmentation with synthetic data addresses distribution shifts in spectral imaging - Qasim, Ahmad Bin; Motta, Alessandro; Studier-Fischer, Alexander; Sellner, Jan; Ayala, Leonardo; Hübner, Marco; Bressan, Marc; Özdemir, Berkin; Kowalewski, Karl-Friedrich; Nickel, Felix; Seidlitz, Silvia; Maier-Hein, Lena (International journal of computer assisted radiology and surgery, 2024)
Purpose: Surgical scene segmentation is crucial for providing context-aware surgical assistance. Recent studies highlight the significant advantages of hyperspectral imaging (HSI) over traditional RGB data in enhancing segmentation performance. Nevertheless, the current hyperspectral imaging (HSI) datasets remain limited and do not capture the full range of tissue variations encountered clinically. Methods: Based on a total of 615 hyperspectral images from a total of 16 pigs, featuring porcine organs in different perfusion states, we carry out an exploration of distribution shifts in spectral imaging caused by perfusion alterations. We further introduce a novel strategy to mitigate such distribution shifts, utilizing synthetic data for test-time augmentation. Results: The effect of perfusion changes on state-of-the-art (SOA) segmentation networks depended on the organ and the specific perfusion alteration induced. In the case of the kidney, we observed a performance decline of up to 93% when applying a state-of-the-art (SOA) network under ischemic conditions. Our method improved on the state-of-the-art (SOA) by up to 4.6 times. Conclusion: Given its potential wide-ranging relevance to diverse pathologies, our approach may serve as a pivotal tool to enhance neural network generalization within the realm of spectral imaging.
Gesehen am 29.07.2024